TINGKAT LAJU INFILTRASI TANAH PADA DAS KRUENG MANE KABUPATEN ACEH UTARA - Delima Delima; Halim Akbar; Muhammad Rafli (Faculty of Agriculture, Universitas Malikussaleh, 2018)
Infiltration is the inclusion of water into the soil through the soil surface due to differences in matrix potential, gravitational potential and pressure potential Infiltration is an important component in soil conservation. It is because the efforts are fundamental in managing the relationship between rainfall intensity and infiltration capacity, as well as run off. The magnitude of surface flows due to disruption of characteristics and potential land will change the ecosystem which can reduce the function of river basin (DAS). This study aims to measure the infiltration rate in the Krueng Mane watershed in North Aceh District. The method used in this research was survey method where to measure infiltration rate using infiltrometer method. The results revealed that the highest infiltration rate was 8.20 cm / h. It was found in mixed plantation land cover, 0-3% slope and latosol soil type. The lowest infiltration rate was 1.906 cm/h, found in oil palm plantation cover, slope of 3-8% and yellow podzolic soil type (PMK). Soil texture is dominated by clay fraction, porosity value is 43,23-45,56%, moisture content is between 1.01-4,38%, C-organic content is 0,32-2,93%, soil permeability is 0, 28-11.12 cm / hour and bulk density ranged from 1.13 to 1.35 gr / cm³. The result of statistical analysis indicated that the fraction of dust had a positive correlation with the C-organic content (r = 0.851 **). The porosity of the soil is positively correlated with the permeability (r = 0.844 **).